Collaborative training to improve beef cattle farmers’ technical competency in West Pasaman District - Fuad Madarisa, Melinda Noer Asmawi, Jafrinur (Universitas Andalas, 2017)
At the end of 2015, this study has been conducted to describe the planning; process; and evaluation of collaborative training using a comparative approach, 220 and 44 beef cattle farmers participated as informant in both types of - collaborative and non-collaborative training respectively. Fifteen informants representing stakeholder provided primary data. Both primary and secondary data were analyzed by using qualitative and quantitative approaches. The results showed that planning was based on an effort to accomplish the discrepancy of cattle farmer technical competency to perform breeding program. Process of conducting collaborative training focused on group management and keeping beef cattle. In non-collaborative training was on recording technics to prepare the issue of breeding cattle certificate. Collaborative training was assisted by a number of stakeholder facilitators, but, non-collaborative training was carried out by facilitators from an institution. Improvement of farmer technical competency has shown by adding of 58.41 % of cattle population, although there was an increasing of participant cognitive domain by 43.53 % at collaborative training. The recommendation advised that management and keeping cattle technical competency are continiously acquired for the half of groups (54.5%), while recording improvement should be taken into account at all groups (100 %).